Multicriteria Approach to Determining the Optimal Composition of Technical Means in the Design of Sea Grain Terminals - Rudenko, Sergey; Shakhov, Anatoliy; Lapkina, Inna; Shumylo, Oleksandr; Malaksiano, Mykola; Horchynskyi, Ihor (Transactions on Maritime Science, 2022)
The main aim of the article is to develop technique for determining the optimal equipment of a sea grain terminal with technical means at the stage of its design. In many works, in order to study the performance of transport systems operating under conditions when the loading level is subject to random fluctuations, the queuing theory methods and random processes are used. However, in a number of cases this approach does not allow to take into account all specifics of the processes that significantly affect sea terminals performance. Also, most of the available studies aim at enhancing a certain single key performance indicator (it can be total costs, performance, income, etc.) to its maximum, provided that the other indicators are within the permissible range of values. However, in many cases, there are more than one key performance indicator which need to be improved. Since the queuing theory and single criterion optimization methods did not allow to achieve the desired results, to study the problem, a technique was introduced based on the combination of simulation modelling and multicriteria optimization methods, which allows us to take into account all the main features of operations at grain terminals. To assess the terminal economic efficiency, the Equivalent Annual Cost indicator was used. The relationship between the cargo unit transshipment cost and the average processing time of consignments is analyzed, provided that the cargo flow intensity is subject to random fluctuations. Using this relationship, a technique for determining the optimal composition of grain terminal equipment was introduced, based upon the multicriteria optimization and simulation modelling methods. The developed technique makes it possible to determine the qualitative and quantitative choice of equipment for a sea grain terminal, taking into account both the cargo transshipment cost and the processing time of consignments. The studies have shown that, with an appropriate choice of the terminal equipment, it is possible to significantly reduce the time of cargo handling due to only a slight increase in the cargo unit transshipment cost.